ESSENTIAL REQUIREMENTS FOR IMPLEMENTING STRATEGIC HUMAN RESOURCE MANAGEMENT AT THE MINISTRY OF YOUTH AND SPORTS IN IRAQ AND IDENTIFYING ORGANIZATIONAL IMPROVEMENT PRIORITIES - Roula Adil Jawad; Dr. Mourad Mohammed Bahloul (Proximus Journal Publishing, 2025)
This study aimed to identify the essential requirements for implementing strategic human resource management (SHRM) at the Ministry of Youth and Sports in Iraq. The researcher employed a descriptive survey methodology using both personal interviews and online (electronic) questionnaires to suit the nature of the study and achieve its objectives and research questions. The research sample was selected intentionally and included 276 individuals from Ministry employees as well as stakeholders from clubs and sports federations in Iraq. The exploratory study was conducted on twenty-three individuals, while the main study included 253 participants. Data were collected and analyzed statistically using the social and psychological research software SPSS v.25, providing various statistical analyses. The study concluded that the essential dimensions for implementing SHRM at the Ministry included: strategic thinking, strategic analysis, strategy formulation, strategy implementation, and strategy monitoring and evaluation
Keywords: Strategic management; human resources; Ministry of Youth and Sports